Dehalogenation of 4 — Chlorobenzoic Acid by Pseudomonas isolates - Banta, G. (Springer-Verlag, 2007)
Twenty three bacterial isolates either pure or consortium were initially screened on the basis of their ability to degrade as well as dechlorinate 4 — chlorobenzoic acid (4-CBA). Based on comparative growth response, three pure isolates Pseudomonas putida GVS-4, Pseudomonas aeruginosa GVS-18 and Pseudomonas aeruginosa GWS-19 and a consortium SW-2 was finally selected for further studies. The enzyme studies performed with cell free extracts revealed that dehalogenase activity was substrate specific with maximum activity at 300 μgml(−1) substrate concentration. Catechol 1,2 dioxygenase activity was found to be present in cell free extracts suggesting that 4 — chlorobenzoic acid (4-CBA) is catabolized by ortho-ring cleavage pathway. The dehalogenase enzyme profile showed single enzyme band in case of GVS-4 (Rm 0.76), GVS-18 (Rm 0.84), GWS −19 (Rm 0.85) and two bands in SW-2 (Rm 0.71 & 0.10).